Data quality improvement of student data submission to mymohes - Majina, Binti Sulaiman (Faculty of Computer Science and Information Technology, 2012)
MyMoheS system is a data collecting system that has been established by the Ministry of Higher Education (MoHE) for the purpose of publication in order to generate information and knowledge that will indicate the true developmental progress in the national higher learning sector. Thus, each institutional higher learning (IHL) in Malaysia strives to enhance the credibility of the supplied data and to ensure data quality of the institution remains at a good level. Hence, each supplied data is reviewed and evaluated on the level of data quality so that the data will exclude inconsistent data, blank field data, unspecified status and incomplete information before submission by the IHL.